2022
DOI: 10.1097/ppo.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus–Directed Therapeutics for Human Papillomavirus–Associated Oropharyngeal Cancer

Abstract: Despite the availability of prophylactic human papillomavirus (HPV) vaccines, there is a growing incidence of HPV-associated head and neck squamous cell carcinomas (HPV-HNSCC) worldwide. The viral etiology of HPV-HNSCC provides an opportunity to develop personalized immune-based therapies, which target the unique viral- or tumor-specific proteins. Novel HPV-targeted immunotherapeutic approaches in clinical development are reviewed. Early results from these trials highlight new opportunities and potential chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Therapeutic vaccines directed to HPV-associated malignancies should induce a specific cellular immune response against tumor antigens [ 29 ]. Therapeutic vaccines offer treatment and immune enhancement options for individuals already infected with HPV [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic vaccines directed to HPV-associated malignancies should induce a specific cellular immune response against tumor antigens [ 29 ]. Therapeutic vaccines offer treatment and immune enhancement options for individuals already infected with HPV [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The in silico analysis is an attractive strategy to develop therapeutic vaccines against infectious and non-infectious diseases. Prediction of functional and conserved B- and T-cell epitopes using the immunoinformatics tools could help generation of novel multiepitope constructs stimulating both humoral and cellular immunity [ 29 ]. The studies showed that heat shock proteins can form stable complexes with TAAs in tumor cells, and thus facilitate antigen uptake through HSP receptors by the APCs [ 4 , 31 ].…”
Section: Discussionmentioning
confidence: 99%